2005
DOI: 10.4102/curationis.v28i4.1021
|View full text |Cite
|
Sign up to set email alerts
|

An assessment by nurses and mothers of a ‘road-to-health ’ book in the Western Cape

Abstract: Objectives: To evaluate English, Afrikaans, and Xhosa mother-retained ‘Road-to- Health Book’ (RTH book) for children, and an electronic calculator.
Design: Researchers D Harrison (DH) and H Harker (HH) informed clinic staff about the contents and significance of the RTH book. They requested nurses to use this book in conjunction with the Road-to-Health Card and to issue and explain its use to every visiting client. The use of an electronic calculator that plotted horizo…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…18,19 Our sources echoed existing studies advocating that HBRs should be created in regional languages. For example, the Road to Health card in South Africa was printed in English, Afrikaans, and Xhosa, 21 and the Patient Passport in the USA had better impact when there was a concurrent Spanish version. 35 An informal review conducted by Brown showed that the health messages in HBRs were often poorly aligned to national literacy levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Our sources echoed existing studies advocating that HBRs should be created in regional languages. For example, the Road to Health card in South Africa was printed in English, Afrikaans, and Xhosa, 21 and the Patient Passport in the USA had better impact when there was a concurrent Spanish version. 35 An informal review conducted by Brown showed that the health messages in HBRs were often poorly aligned to national literacy levels.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature has examined selected aspects of implementation, some slightly more than others, namely design of the HBR 2,[16][17][18][19][20] and promotion of end user engagement. [21][22][23][24] However, substantial operational challenges still remain even in these areas and require further research. 14,25 The majority of existing literature studied HBRs in high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being useful in the follow up of individual child health care through the referral ladder the notes can also serve as a database for future research. Despite some limitations in recording disease data (Tarwa & Villiers, 2007) other studies have shown such a book to be acceptable by the majority of the health workers and clients (Harrison et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[6] Numerous international and local studies have highlighted three weak links in the use of the PCHR by health professionals: failure to request the record from the caregiver, failure to use the record as a reference source of the child's medical background, and failure to comprehensively and accurately record new information in the record. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Much of the research on the weak links has relied on participant recall, which in many cases has not matched the health professional's medical notes. Few studies have examined both the PCHR and institutional clinical records to determine what information has been transferred in either direction.…”
Section: Researchmentioning
confidence: 99%